2001
DOI: 10.1021/ci010323u
|View full text |Cite
|
Sign up to set email alerts
|

A Fuzzy ARTMAP Based on Quantitative Structure−Property Relationships (QSPRs) for Predicting Aqueous Solubility of Organic Compounds

Abstract: Quantitative structure-property relationships (QSPRs) for estimating aqueous solubility of organic compounds at 25°C were developed based on a fuzzy ARTMAP and a back-propagation neural networks using a heterogeneous set of 515 organic compounds. A set of molecular descriptors, developed from PM3 semiempirical MO-theory and topological descriptors (first-, second-, third-, and fourth-order molecular connectivity indices), were used as input parameters to the neural networks. Quantum chemical input descriptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 59 publications
0
58
0
Order By: Relevance
“…Fuzzy ARTMAP Neural Network Systems. The present fuzzy ARTMAP neural network system was recently introduced for developing QSPRs for boiling temperatures, 18 critical properties, 19 aqueous solubilities, 20 and octanol-water partition coefficients. 21 This fuzzy ARTMAP network is the modification introduced by Giralt et al, 27,36 to the original model of Carpenter et al [22][23][24][25][26] Additional information about fuzzy ART and fuzzy ARTMAP systems can be found elsewhere.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fuzzy ARTMAP Neural Network Systems. The present fuzzy ARTMAP neural network system was recently introduced for developing QSPRs for boiling temperatures, 18 critical properties, 19 aqueous solubilities, 20 and octanol-water partition coefficients. 21 This fuzzy ARTMAP network is the modification introduced by Giralt et al, 27,36 to the original model of Carpenter et al [22][23][24][25][26] Additional information about fuzzy ART and fuzzy ARTMAP systems can be found elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…The advantage of NNs, over classical regression analysis methods, is their inherent ability to incorporate nonlinear relationships between chemical structural parameters and physicochemical properties. [16][17][18][19][20][21] Neural network/QSPR models for estimating the Henry's Law constant for a data set of 357 organic compounds (-7.08 e logH e 2.32) have been recently reported by English and Carroll (2001). 16 The above authors reported QSPRs based on 12-4-1 and 10-3-1 backpropagation neural network architectures (trained using 303 compounds) that performed with absolute errors of 0.237 and 0.281 logH units for the test set (54 compounds), respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first approach [4][5][6][7][8] is to build model from more easily measured physicochemical properties, such as melting point, boiling point, molar volume, partition coefficient, chromatographic retention time, etc. The other method is based on the information from the molecular of the organic chemicals, which can be further divided into two classes, one is group contributions method [9][10][11][12] and the other is QSPR approach [1,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Backpropagation neural networks have recently emerged as an alternative for the development of QSPRs and quantitative structure-activity relationships (QSARs) to predict physicochemical properties and biological activities, respectively (Bünz et al, 1998;Chow et al, 1995;Egolf and Jurs, 1993;Espinosa et al, 2000Espinosa et al, , 2001aGakh et al, 1994;Hall and Story, 1996;Mitchell and Jurs, 1998;Simamoea et al, 1993;Stanton and Jurs, 1990;Stanton et al, 1991;Viswanadhan et al, 2001;Yaffe et al, 2001Yaffe et al, , 2003. This alternative modeling strategy for QSPR development yields significantly higher prediction accuracy compared to that of traditional regressionbased correlations.…”
Section: Introductionmentioning
confidence: 99%